Molecular mechanism of vasculogenic mimicry in tumors - Li, Wen; Liu, Jianrong; Ren, Jianlin; Li, Qi; Hou, Feng Gang (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Vasculogenic mimicry (VM) is a new model of tumor angiogenesis, which refers to the de novo formation of perfusable, matrix-rich, vasculogenic-like networks by virtue of the plasticity of aggressive tumor cells and the reconstruction of extracellular matrix (ECM). However, little is known about the molecular underpinnings of this phenomenon. To sum up, interactions of the critical VM-modulating pathways such as vascular (VE-cadherin, EphA2, VEGFR), embryonic and/or stem cell (Nodal, Notch4, CD133+, CD271), and hypoxia-related (HIF-1α, Twist1) signaling pathways are necessary for the formation of vasculogenic mimicry. What is more, accompanied by anti-angiogenic therapy of tumors, the use of VM is becoming more and more important.